The association between audit firm characteristics and fraudulent financial reporting: Malaysian fraud cases / Safinah Iberahim - Iberahim, Safinah (2013)
The objective of this study is to examine the association between audit firm characteristics and fraudulent financial reporting. This study used matched-sample logistic regression of 122 companies with and without fraudulent financial reporting over a 5-years period from 2006 to 2010 and empirically examines whether the audit tenure, audit fees, audit firm size and auditor industry specialization will influence the audit quality, thus affect the company's financial reporting. The results support prior findings by indicating a negative relation between the audit fees and the likelihood of fraudulent financial reporting. In addition to that, the findings also show that auditor industry specialization is also related to the propensity of fraud in financial reporting. On the other hand, no significant evidence was found for audit tenure and audit firm size, leading us to conclude that these factors are not an important indicator of the quality of financial reporting. This study also found that the company with higher leverage and more loss recognition is most likely to involve in fraudulent financial reporting. The result is robust even after including various controls such as year effect and industry effect. This study concludes that paying high audit fees and engaging an auditor industry specialist, will result in increase of audit quality, thus reducing the likelihood of fraudulent financial reporting.